Devolved agricultural extension services in the Philippines trials and triumphs : cases from frontline local governments - Brillantes, Alex B.; Ocenar, Remigio D. 1949-; Tumanut, Michael A. (Center for Local and Regional Governance, National College of Public Administration and Governance, University of the Philippines, 2007)
"This book is about the impact of devolution on the delivery of agricultural extension services in the Philippines. It is a product of a project supported by the Australian Centre for International Agricultural Research, and jointly conducted by the Center for Local and Regional Governance (CLRG) of the National College of Public Administration and Governance, University of the Philippines, and the Australian-based Centre for International Economics. They look at agricultural extension through the eyes of public administrators and academics specializing in regional-central relations, an economist and an extension specialist."--Preface.